CONTEXT MATHEMATICAL PROBLEMS IN THE FORMATION OF CORE COMPETENCES OF ENGINEERING STUDENTS - Olga V. Yanuschik; Victor А. Dalinger (Высшее образование в России)
The paper highlights the experience of Tomsk Polytechnic University (TPU) in teaching mathematics to engineering students using problem solving method. The article presents the concepts "core competence" and "task context" and shows their place in the educational process. It was shown that composing of contextual math tasks by students within conference week promotes deeper acquisition of subject and professional knowledge and skills. This method also promotes the formation of students' core competences.